Peduncle‐girdling of Shiraz (Vitis vinifera L.) bunches and sugar concentration at the time of girdling affect wine volatile compounds. (28th November 2017) - Böttcher, C.; Boss, P.K.; Harvey, K.E.; Burbidge, C.A.; Davies, C.
Abstract: Background and Aims: The climate change‐related acceleration of grape ( Vitis vinifera L.) berry 'sugar‐ripeness' requires an improved understanding of the relationship between berry sugar concentration and wine flavour and aroma. Methods and Results: Peduncle‐girdling of Shiraz bunches at three post‐veraison stages identified sugar‐related changes to grape metabolites associated with ripening and to wine volatile compounds. Restricting sugar uptake at 10–14°Brix had severe effects on the accumulation of eight amino acids, cytokinins and, by inference, the cellular redox status. Consequently, wine made from these berries displayed changes to a large number of compounds and compound classes, in particular esters, higher alcohols and C13 ‐norisoprenoids, which would potentially result in a substantial difference in wine flavour and aroma. When grapes reached 18°Brix, however, peduncle‐girdling caused only minor modification of berry amino acid concentration and wine volatile composition. By comparing wines made from berries of peduncle‐girdled bunches with those made from berries where ripening was delayed by auxin treatments, a small group of volatile compounds was identified that universally responds to treatments delaying sugar accumulation in grapes. Conclusions: The findings suggest that once berries have reached a modest sugar concentration, prevention of further sugar uptake even by an invasive treatment, such as girdling, has minimal impact on wine volatile composition. Significance of the Study: This study confirms that the manipulation of sugar accumulation can mitigate climate change‐related acceleration of sugar‐ripeness in warm to hot wine regions while maintaining the volatile composition of wine.